2011
DOI: 10.1371/journal.pone.0017425
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Brucella abortus Recombinant In Vivo-Induced Antigens Reduces Bacterial Load and Promotes Clearance in a Mouse Model for Infection

Abstract: Current vaccines used for the prevention of brucellosis are ineffective in inducing protective immunity in animals that are chronically infected with Brucella abortus, such as elk. Using a gene discovery approach, in vivo-induced antigen technology (IVIAT) on B. abortus, we previously identified ten loci that encode products up-regulated during infection in elk and consequently may play a role in virulence. In our present study, five of the loci (D15, 0187, VirJ, Mdh, AfuA) were selected for further characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This, however, is the singular example in which vaccination against the microbial activator of IL-10R signaling induces protective efficacy (i.e., vaccine-induced reductions in infection and/or disease). In contrast, vaccination of mice with either the YopM type III secretion system protein of Yersinia pestis or the PrpA virulence factor of Brucella abortus does not induce any protective efficacy against bacterial challenge (46,47). Since, in the case of YopM, purified protein can enter into the cell by "autonomous translocation" (48), vaccination with an unmodified form of the protein may preclude the efficient induction of antibodies that neutralize the function of the protein during primary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This, however, is the singular example in which vaccination against the microbial activator of IL-10R signaling induces protective efficacy (i.e., vaccine-induced reductions in infection and/or disease). In contrast, vaccination of mice with either the YopM type III secretion system protein of Yersinia pestis or the PrpA virulence factor of Brucella abortus does not induce any protective efficacy against bacterial challenge (46,47). Since, in the case of YopM, purified protein can enter into the cell by "autonomous translocation" (48), vaccination with an unmodified form of the protein may preclude the efficient induction of antibodies that neutralize the function of the protein during primary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of brucellae to survive within macrophages is essential for their virulence (Celli and Gorvel, 2004). In the past few years, hundreds of virulence-related genes have been identified by transposon mutagenesis (Wu et al, 2006), in vivo-induced antigen technology (Lowry et al, 2011), DNA microarray hybridization (Tian et al, 2013), and bioinformatics (He, 2012), which include lipopolysaccharide (Seleem et al, 2008), the type IV secretion system T4SS (Seleem et al, 2008;Martirosyan et al, 2011), the quorum-sensing-related transcriptional regulator VjbR , the BvrR/BvrS two-component regulatory system (Sola-Landa et al, 1998;Martinez-Nunez et al, 2010), and the periplasmic cyclic -1,2 glucans (Briones et al, 2001), among others. Interestingly, most of these genes are not direct virulence factors, but are transcription regulators, such as VjbR which can control the expression of virulence factors to affect Brucella virulence .…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, it has been reported that purified YopM can undergo "autonomous translocation" into the interior of mammalian cells (Ruter et al 2010). Vaccination/challenge results comparable to those observed for YopM were noted for immunization with the PrpA virulence factor of B. abortus (Lowry et al 2011), a protein that acts as a B cell mitogen and stimulates expression of cIL-10 ( Spera et al 2006). Despite eliciting high binding antibody titers, mice immunized with wild-type PrpA were not protected from B. abortus challenge.…”
Section: Preventive Vaccination Against Microbial Activators Of Il-10mentioning
confidence: 66%